An Analysis of Interference from Javanese in the Pronunciation of ,  and  in English by the Students of Faculty of Letters in Gajayana University - Dewi, Pradnya Paramita (ELTICS : Journal of English Language Teaching and English Linguistics, 2014)
AbstrackEnglish  as one of the international languages has been learned by the students of Faculty of Letters in Gajayana University. In learning English as foreign language, most learners have problem  in  pronunciation,  especially  in  the  way  they  pronounce  the  sound  of  the  target language.  Mispronunciations  which are produce by the learners is caused by the interference of the source language or first language. The object  of this research  is the students of Faculty of Letters in Gajayana University 2005/2006 intake who are  native speakers of Javanese  and have  been  done  phonology  class.  Some  specific  sounds  are  discussed  in  these  research namely  English  sounds  of  inter-dental  fricative,    and  alveolar  approximant.  The finding of the research are  some interferences occur in pronouncing  those sounds, they are 1) voiceless  inter-dental  fricative    is  pronounced  using  voiceless  dental  stop  ,  aspirated voiceless dental stop  , voiced dental stop  , and voiceless palato-alveolar affricate  . 2).Voiced  inter-dental  fricative  is  pronounce  using  voiceless  dental  stop  ,  aspirated voiceless dental stop  , voiced dental stop  , and voiceless palato-alveolar affricate  . 3).Voiced  alveolar  approximant    is  pronounced  using  voiced  alveolar  trill.  4).  thepossible reasons for the interferences made are based on the similarity of characteristics in the state of vocal cords, place of articulation, and manner of articulations.Keyword: interference